2009
DOI: 10.1007/s00423-009-0541-5
|View full text |Cite
|
Sign up to set email alerts
|

General and visceral surgery practice in German hospitals: a real-time work analysis on surgeons’ work flow

Abstract: For the first time, surgeons' workflow in German hospitals was studied in real time. The study results substantiate physicians' statements about their own working conditions, especially with concerns to large amount of time spent on administration tasks. The findings of this study form a basis upon which further analysis can be built and recommendations for improvements in physicians' workflows at German hospitals can be made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 23 publications
3
25
0
3
Order By: Relevance
“…Previous studies carried out in German hospitals analyzed doctors' working conditions and job satisfaction in various hospitals [26][27][28][29][30][31][32][33][34][35][36][37]. A number of studies focused on German emergency departments using surveys on the quality of medical treatment to evaluate hospital performance and working environments [38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies carried out in German hospitals analyzed doctors' working conditions and job satisfaction in various hospitals [26][27][28][29][30][31][32][33][34][35][36][37]. A number of studies focused on German emergency departments using surveys on the quality of medical treatment to evaluate hospital performance and working environments [38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of real-time work of German surgeons indicated that their working day is more dominated by documentation duties and administrative workload than by being in the operation theatre or spending time with patient care [16,17]. As our data shows, participation rate of surgical residents remained constant within the observation period, whereas cumulative working time as well as participation rates of medical students in the operating room decreased, and the rate of operations performed without any second assistant increased over the years.…”
Section: Discussionmentioning
confidence: 69%
“…Whereas in the late 1990s, the relationship between job candidate and place of employment was 12.3:1 in German academic hospitals; nowadays, the shortage of surgical residents has become evident [12,18]. Poor quality of life [19,20], as well as long education times and a very high amount of paperwork compared to the limited operative workload, have been mentioned as the underlying causes [16,21,22]. Hence, 50% of all medical students who were initially interested in surgery change their opinion and attitude during their medical studies [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Das Patientenaufkommen steigt stetig und das Arbeitsaufkommen von Chirurgen wird Schätzungen zufolge bis zum Jahr 2020 (Basisjahr 2000) um knapp 40% über dem heutigen liegen [11,12]. Behandlungs-und Verwaltungsabläufe in der Chirurgie sind komplex.…”
Section: Introductionunclassified